Enhanced ferroelectric and piezoelectric characteristics in Ca-substituted ceramics - S. B. Chen; S. Y. Wu; X. M. Chen (Journal of Advanced Dielectrics, 2022)
In this work, Ba[Formula: see text]Ca[Formula: see text]Ti[Formula: see text]Zr[Formula: see text]O3 ([Formula: see text]= 0.00–0.25) ceramics were prepared by a solid-state reaction method, and the variation of dielectric, ferroelectric and piezoelectric characteristics has been investigated together with the structure evolution. The crystal structure varies from rhombohedral to tetragonal at room-temperature and the morphotropic phase boundary (MPB) is determined around [Formula: see text]= [Formula: see text]0.10, where the significantly enhanced ferroelectric and piezoelectric properties are achieved. With the increase of Ca content, the system gradually evolves into a relaxor ferroelectric. This work provides useful guidance for future research on lead-free piezoelectric materials.